Carbon-loaded nano-alloy catalyst, and preparation method and hydrogenation application thereof

By combining Pd or Pt with iron, cobalt, nickel and copper transition metals in a carbon-supported catalyst, the nano-alloy catalyst is prepared, which solves the problem of decreasing the activity and selectivity of the existing catalysts, and achieves an efficient and stable phenol hydrogenation reaction, and reduces the cost of the catalyst.

CN119771431APending Publication Date: 2025-04-08LIAOCHENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411848424.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing catalysts have problems of decreased activity and selectivity in phenol selective hydrogenation reaction, and precious metal catalysts are costly and difficult to recover.

Method used

Using carbon-supported nanoalloy catalysts, PdFeCuCoNi/C and PtFeCuCoNi/C catalysts are prepared by combining Pd or Pt with iron, cobalt, nickel and copper transition metals, and the stability and activity of the catalyst are improved by combining liquid phase reduction and high-temperature heat treatment.

Benefits of technology

The formation of cyclohexanone and cyclohexanol is achieved efficiently in phenol selective hydrogenation reaction. The catalyst has excellent catalytic stability and high atomic utilization rate, reducing the loss and cost of precious metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771431A_ABST
    Figure CN119771431A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-alloy catalyst based on carbon loading and a preparation method and hydrogenation application thereof, a carbon-loaded PdFeCuCoNi nano-particle catalyst and a carbon-loaded PtFeCuCoNi nano-particle catalyst are successfully prepared by using a liquid phase reduction and high-temperature heat treatment combined method under the protection of argon, and compared with traditional Pd and Pt-based catalysts, the carbon-loaded PdFeCuCoNi nano-particle catalyst and the carbon-loaded PtFeCuCoNi nano-particle catalyst have the advantages that the carbon loading capacity is greatly improved; according to the invention, transition metals such as iron, cobalt, nickel and copper are compounded with traditional noble metals such as Pt and Pd, the obtained carbon-loaded nano-alloy catalyst has an excellent catalytic effect on selective hydrogenation of phenol, and the nano-alloy catalyst has excellent catalytic stability due to the comprehensive action of a highly ordered crystal structure and high entropy; the nano-alloy catalyst is low in cost, the preparation method is simple, and the nano-alloy catalyst has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanomaterials, and in particular to a carbon-loaded nano alloy catalyst, a preparation method thereof and hydrogenation application thereof. Background Art

[0002] Cyclohexanone / cyclohexanol are widely used chemical raw materials. As key synthetic intermediates for the production of nylon, fuel, medicine, plasticizer, surfactant, solvent, etc., they have broad prospects in the future chemical industry. The hydrogenation reaction of phenol is the key reaction to produce cyclohexanone and cyclohexanol. Cyclohexanone and cyclohexanol are basic intermediates for the synthesis of various products. In this reaction, the development of efficient catalysts and the improvement of production processes are the research focus. [1] The catalysts used in the hydrogenation of phenol to produce cyclohexanone mainly include transition metals such as Pd, Ru, Cu, Yt, Ni and Pt. Among them, Pd shows good selectivity and activity in the selective hydrogenation of phenol to produce cyclohexanone. [2] , has excellent hydrogen activation performance, has the strongest hydrogen absorption capacity among platinum group metals, and the dissolved hydrogen will be completely released at high temperature. Considering the price and reaction results, Pd has become one of the most studied precious metals in the selective hydrogenation of phenol. [3] .

[0003] Catalytic hydrogenation plays an important role in industrial processes and is widely used in petrochemical and environmental industries. Platinum group metals have high activity in hydrogenation of saturated benzene rings and have been widely used in ECH and thermal catalytic hydrogenation (TCH) of lignin model compounds. [4] Electrocatalytic hydrogenation offers a sustainable pathway to the robust production of specialty chemicals and transportation fuels [5] In the electrochemical hydrogenation (ECH) strategy, active hydrogen is generated in situ from water on the surface of the electrocatalyst and participates in the hydrogenation of the adsorbed organic substrate under ambient conditions by utilizing the electrical properties in the protic medium.

[0004] Non-precious metals have large reserves and low prices. If they can achieve high selectivity, stability and conversion rate in the selective hydrogenation of phenol, they will have very broad application prospects. [6] It is mentioned that Ni has high chemical activity and can absorb a large amount of hydrogen. Ni shows structural sensitivity in the hydrogenation reaction of aromatic compounds, and the results vary with the average particle size. Although Ni catalysts have high catalytic activity and low price, the product in the phenol hydrogenation reaction is usually cyclohexanol.

[0005] Precious metals, especially platinum group metals, have good chemical stability, oxidation resistance and corrosion resistance. They have strong ability to adsorb and activate hydrogen, and are a good choice for the selective hydrogenation of phenol. Pd has excellent performance in hydrogen activation. Applying Pd to the reaction of selective hydrogenation of phenol to produce cyclohexanone and cyclohexanol can greatly improve the catalytic activity. [7] . Chen Chen [8] et al. prepared Pd / C catalyst by impregnation method and studied the effects of activated carbon pretreatment method, precipitation temperature and reduction method on the catalyst in the gas phase hydrogenation of phenol to cyclohexanone. Although Pd-based catalysts can well adsorb hydrogen in the reaction and activate it, there are still some disadvantages. For example, impurities such as carbon monoxide, arsenide, sulfide and some components generated by side reactions can poison the palladium catalyst, reducing its activity and selectivity; as a member of the precious metal platinum group metal, it is relatively expensive. [9] ; Palladium-based catalysts will be deactivated during use due to the aggregation of catalyst nanoparticles and changes in the lattice. At present, researchers have proposed a variety of innovative response strategies to improve the reaction performance of Pd-based catalysts in phenol hydrogenation to cyclohexanone. Yin Defu

[10] et al. proposed a "vertical-horizontal alliance" strategy to improve the conversion rate of cyclohexanone in the phenol hydrogenation reaction. [6] The PdLa / SiO2-1 catalyst prepared with nano-silica as the carrier showed high selectivity and conversion rate in the selective hydrogenation reaction of phenol. It has the advantages of high specific surface area, good dispersibility, easy recovery and reusability.

[0006] The hydrogenation of phenol is a key reaction to produce cyclohexanone and cyclohexanol, which are basic intermediates for the synthesis of various products. Various types of metal catalysts are studied, developed and continuously improved for this reaction. Many reported catalysts are limited in practical or large-scale application due to their low activity or selectivity and their non-recyclability. Therefore, the development of new and more suitable catalytic systems that can carry out this process under milder reaction conditions and, most importantly, be able to switch between the production of cyclohexanone or cyclohexanol remains a major challenge.

[0007] References

[0008] [1]MaryamAkbari,BabakKarimi,et al.Switchable cyclohexanone / cyclohexanol selectivity inroom temperature aqueous hydrogenations ofphenolusing Au-Pdnanoparticles supported on abimodal cubic N,S-doped mesoporouscarbon[J].Sustainable Chemistry and Pharmacy Volume39,2024.PP 101572-.

[0009] [2] Li Xuerong. Research on mesoporous carbon-supported Pd catalyst for selective hydrogenation of phenol[D]. Shanghai Normal University, 2022. DOI: 10.27312 / d.cnki.gshsu.2022.001866.

[0010] [3]Hui Chen,Jinsheng Sun.Selective hydrogenation ofphenol forcyclohexanone[J].IndustrialandEngineering ChemistryVolume 94,2021,Pages 78-91,ISSN 1226-086X.

[0011] [4]Ling Zhou,Xiaorong Zhu,et al.Identification of the hydrogenutilization pathway for theelectrocatalytic hydrogenation ofphenol[J].ScienceChina Chemistry September 2021Vol.64No.9:1586-1595.

[0012] [5]James Akinola,Isaiah Barth,et al.Electrocatalytic hydrogenation ofphenol onplatinum-cobalt alloys[J].Journal ofCatalysis 430(2024)115331.

[0013] [6] Xu Junyuan. Synthesis of palladium-based nanocatalysts and their catalytic performance in selective hydrogenation of phenol[D]. Jiangxi University of Science and Technology, 2023. DOI: 10.27176 / d.cnki.gnfyc.2023.000456.

[0014] [7] Deng Xin. Synthesis of palladium-based nanocatalysts and their catalytic performance in hydrogenation of 4-nitrophenol[D]. Jiangxi University of Science and Technology, 2023. DOI: 10.27176 / d.cnki.gnfyc.2023.000364.

[0015] [8] Chen Chen, Jin Hanqiang. Effect of preparation conditions of palladium-carbon catalyst on gas phase hydrogenation of phenol to cyclohexanone[J]. Energy and Chemical Engineering, 2015, 36(06): 1-4.

[0016] [9] Zhang Ben. Synthesis and electrochemical characterization of palladium-based bimetallic nanocrystalline catalysts[D]. Qingdao University, 2023. DOI: 10.27262 / d.cnki.gqdau.2023.000741.

[0017]

[10] Yin Defu. Study on the directional preparation of cyclohexanone by hydrogenation of phenol catalyzed by Pd-based core-shell catalysts[D]. Qingdao University of Science and Technology, 2023. DOI: 10.27264 / d.cnki.gqdhc.2022.001075. Summary of the invention

[0018] The technical problem to be solved by the present invention is to provide a carbon-loaded nano alloy catalyst, a preparation method thereof and hydrogenation application thereof in view of the deficiencies in the above-mentioned prior art.

[0019] In order to solve the above technical problems, the technical solution adopted by the present invention is: In a first aspect of the present invention, a method for preparing a carbon-supported nano alloy catalyst is provided, comprising the following steps:

[0020] S1. Preparation of catalyst precursor:

[0021] M ion solution, Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ The solutions are mixed and ultrasonically dispersed to obtain a mixed solution; wherein the M ion is Pd 2+ or Pt 4+ ;

[0022] S1-2, add carbon powder to the mixed solution, perform ultrasonic treatment, then heat and stir under argon protection, inject sodium borohydride solution under closed conditions, and heat and stir to react under argon atmosphere;

[0023] S1-3, after the reaction is completed, the intermediate product is collected by centrifugation, washed, and then dried under argon protection to obtain a catalyst precursor;

[0024] S2. The catalyst precursor is heated and reduced in a mixed atmosphere of H2 and Ar, and then cooled to room temperature to obtain a carbon-supported nano-alloy catalyst.

[0025] Preferably, step S1-1 is specifically:

[0026] The salt of M ion is dissolved in hydrochloric acid solution to obtain M ion solution; NiSO4.6H2O, FeSO4.7H2O, CoSO4.7H2O, CuSO4.5H2O are dissolved in hydrochloric acid solution to obtain Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ Solution;

[0027] M ion solution, Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ The solutions are mixed and ultrasonically dispersed to obtain a mixed solution;

[0028] Among them, the salt of M ion is Na2PdCl4 or H2PtCl6·6H2O.

[0029] Preferably, step S1-1 is specifically:

[0030] Dissolve 20-360 mg of M ion salt in 3-40 mL of hydrochloric acid solution with a pH of 5-6 to obtain Pd 2+ Solution; 26.5-106mg NiSO4.6H2O, 27.5-110mg FeSO4.7H2O, 28-112mg CoSO4.7H2O, 25-100mg CuSO4.5H2O were dissolved in 10-40mL of hydrochloric acid solution with a pH of 5-6 to obtain Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ Solution;

[0031] Pd 2+ Solution, Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ Take 1-4 mL of each solution, mix, and ultrasonically disperse for 5-20 minutes to obtain a mixed solution.

[0032] Preferably, step S1-2 is specifically:

[0033] Add 57-228 g of carbon powder to the mixed solution, ultrasonically treat for 5-30 min, then heat and stir at 40-60°C under argon protection for 15-60 min, inject 1.5-6 mL of 0.05-0.2 mol / L sodium borohydride solution under closed conditions, heat and stir at 40-60°C under argon atmosphere for 5-26 h.

[0034] Preferably, step S1-3 is specifically:

[0035] After the reaction is completed, the intermediate product is collected by centrifugation at 5000-20000 rpm for 10-40 min, and the intermediate product is washed with deionized water at 5000-20000 rpm for 2-6 times, each time for 2-10 min, and then the intermediate product is dried under argon protection for 4-16 hours to obtain a catalyst precursor; wherein the drying temperature is 80-110°C and the heating rate is 2-8°C / min.

[0036] Preferably, step S2 specifically comprises:

[0037] The catalyst precursor is heated to 400-900°C at a heating rate of 2-8°C / min in a mixed atmosphere of H2 and Ar, reduced for 1-4h, and cooled to room temperature to obtain a carbon-supported nano-alloy catalyst.

[0038] Preferably, the salt of the M ion is Na2PdCl4, and the preparation method of the nano alloy catalyst comprises the following steps:

[0039] S1. Preparation of catalyst precursor:

[0040] S1-1, 40.5 mg Na2PdCl4 was dissolved in 6 mL of hydrochloric acid solution with a pH of 5 to 6 to obtain Pd 2+ Solution; 53mg NiSO4.6H2O, 55mg FeSO4.7H2O, 56mg CoSO4.7H2O, 50mg CuSO4.5H2O were dissolved in 20mL of hydrochloric acid solution with a pH of 5-6 to obtain Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ Solution;

[0041] Pd 2+ Solution, Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ 2 mL of each solution was mixed and ultrasonically dispersed for 10 min to obtain a mixed solution;

[0042] S1-2, add 114 mg of carbon powder to the mixed solution, ultrasonically treat for 15 min, then heat and stir at 50 °C for 30 min under argon protection, inject 3 mL of 0.1 mol / L sodium borohydride solution under closed conditions, heat and stir at 50 °C for 13 h under argon atmosphere;

[0043] S1-3. After the reaction is completed, the intermediate product is collected by centrifugation at 10000 rpm for 20 min, and the intermediate product is washed three times with deionized water at 10000 rpm for 5 min each time, and then the intermediate product is dried under argon protection for 8 h to obtain a catalyst precursor; wherein the drying temperature is 110°C and the heating rate is 4°C / min;

[0044] S2. The catalyst precursor was heated to 400-900°C at a heating rate of 4°C / min in a mixed atmosphere of H2 and Ar, reduced for 2 hours, and cooled to room temperature to obtain a carbon-supported nano-alloy catalyst, denoted as PdFeCuCoNi / C.

[0045] Preferably, the salt of the M ion is H2PtCl6·6H2O, and the preparation method of the nano alloy catalyst comprises the following steps:

[0046] S1. Preparation of catalyst precursor:

[0047] S1-1, dissolve 180 mg H2PtCl6·6H2O in 20 mL of hydrochloric acid solution with a pH of 5 to 6 to obtain Pt 4+ Solution; 53mg NiSO4.6H2O, 55mg FeSO4.7H2O, 56mg CoSO4.7H2O, 50mg CuSO4.5H2O were dissolved in 20mL of hydrochloric acid solution with a pH of 5-6 to obtain Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ Solution;

[0048] Pt 4+ Solution, Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ 2 mL of each solution was mixed and ultrasonically dispersed for 10 min to obtain a mixed solution;

[0049] S1-2, add 114 mg of carbon powder to the mixed solution, ultrasonically treat for 15 min, then heat and stir at 50 °C for 30 min under argon protection, inject 3 mL of 0.1 mol / L sodium borohydride solution under closed conditions, heat and stir at 50 °C for 13 h under argon atmosphere;

[0050] S1-3. After the reaction is completed, the intermediate product is collected by centrifugation at 10000 rpm for 20 min, and the intermediate product is washed three times with deionized water at 10000 rpm for 5 min each time, and then the intermediate product is dried under argon protection for 8 h to obtain a catalyst precursor; wherein the drying temperature is 80°C and the heating rate is 4°C / min;

[0051] S2. The catalyst precursor was heated to 400-900°C at a heating rate of 4°C / min in a mixed atmosphere of H2 and Ar, reduced for 2 hours, and cooled to room temperature to obtain a carbon-supported nano-alloy catalyst, denoted as PtFeCuCoNi / C.

[0052] The second aspect of the present invention provides a carbon-supported nano alloy catalyst, which is prepared by the method as described above.

[0053] The third aspect of the present invention provides a use of the carbon-supported nano alloy catalyst as described above in catalyzing the selective hydrogenation of phenol.

[0054] The beneficial effects of the present invention are:

[0055] The invention provides a carbon-supported nano alloy catalyst, a preparation method thereof and application thereof in catalyzing the selective hydrogenation of phenol. The invention adopts iron, cobalt, nickel and copper transition metals to composite with traditional Pt and Pd noble metals. The obtained carbon-supported nano alloy catalyst has excellent catalytic effect on the selective hydrogenation of phenol. The nano alloy catalyst of the invention has excellent catalytic stability, which is attributed to the comprehensive effect of highly ordered crystal structure and high entropy. The nano alloy catalyst of the invention has low cost, simple preparation method and good application prospect.

[0056] The present invention successfully prepares carbon-supported PdFeCuCoNi nanoparticle catalyst and PtFeCuCoNi nanoparticle catalyst by combining liquid phase reduction and high temperature heat treatment under argon protection, which are respectively recorded as PdFeCuCoNi / C and PtFeCuCoNi / C; compared with traditional Pd and Pt-based catalysts, the Pd / Pt alloy catalyst in the present invention adds transition metals of iron, cobalt, nickel and copper, changes the electronic structure of the catalyst, and optimizes its adsorption and activation ability for phenol; although the alloy catalyst still contains precious metal elements, the cost of the catalyst is reduced to a certain extent by reasonably selecting and matching other metal elements. In addition, the alloy catalyst of the present invention has a higher atomic utilization rate, thereby reducing the loss of precious metals; the present invention provides a new idea for the development of durable and cost-effective palladium-based and platinum-based catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 XRD characterization results of the catalyst PdFeCuCoNi / C prepared in Example 1;

[0058] Figure 2 MCV (cyclic voltammetry), HER (hydrogen evolution reaction) and ECH (electrocatalytic hydrogenation reaction) polarization curves of the catalyst PdFeCoNiCu / C-400°C prepared in Example 1;

[0059] Figure 3 MCV, HER and ECH polarization curves of the catalyst PdFeCoNiCu / C-650°C prepared in Example 1;

[0060] Figure 4 MCV, HER and ECH polarization curves of the catalyst PdFeCoNiCu / C-900°C prepared in Example 1;

[0061] Figure 5 HER and ECH polarization curves in Example 1: (a) PdFeCoNiCu / C-400°C; (b) PdFeCoNiCu / C-650°C; (c) PdFeCoNiCu / C-900°C;

[0062] Figure 6 XRD characterization results of the catalyst PtFeCuCoNi / C prepared in Example 2;

[0063] Figure 7 MCV, HER and ECH polarization curves of the catalyst PtFeCoNiCu / C-400°C prepared in Example 2;

[0064] Figure 8MCV, HER and ECH polarization curves of the catalyst PtFeCoNiCu / C-650°C prepared in Example 2;

[0065] Fig. 9 MCV, HER and ECH polarization curves of the catalyst PtFeCoNiCu / C-900°C prepared in Example 2;

[0066] Fig.10 HER and ECH polarization curves in Example 2: (a) PtFeCoNiCu / C-400°C; (b) PtFeCoNiCu / C-650°C; (c) PtFeCoNiCu / C-900°C. DETAILED DESCRIPTION

[0067] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0068] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0069] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially. 1. In the following examples, the main instruments used are shown in Table 1:

[0070] Table 1

[0071]

[0072] 2. In the following examples, the main reagents used are shown in Table 2 below:

[0073] Table 2

[0074]

[0075]

[0076] 3. Catalyst characterization methods

[0077] In the following examples, X-ray powder diffractometer (XRD) was used to characterize the crystal structure of the catalyst. The test conditions were as follows: the incident radiation was Cu-Kα ( 45KV, 200mA), the test range is 10°-90°.

[0078] 4. Catalyst reaction performance evaluation

[0079] In the following examples, the reaction performance of the catalyst was evaluated in an electrochemical workstation. First, the working electrode in the cathode electrode was prepared: 30 μl of Nafion solution, 2 mg of catalyst, and 360 μl of ethanol solution were mixed, ultrasonicated for 40 min, and loaded on a 1×2 cm carbon paper with a loading area of ​​1 cm 2 Then the battery was assembled: the cathode was a working electrode with carbon paper and a reference electrode (Ag / AgCl), the anode was a counter electrode (platinum mesh), and the electrolyte solution was 60 mL of 0.1 mol / L sulfuric acid solution. The reaction was heated and stirred at 60°C.

[0080] In the following examples, catalyst activation was performed using cyclic voltammetry (Multipie CV), with vertex potential 1 being -0.2 V, vertex potential 2 being -0.8 V, a scan rate being 50 mV / s, and the number of cycles being 5.

[0081] Automatically measure solution resistance using the AC impedance method.

[0082] Catalyst activity was measured by linear sweep voltammetry (LSV). The initial potential was 0 V, the final potential was -1 V, and the scan rate was 0.005 V / s. The current range without IR compensation was 1 A, and the measured value was used under IR compensation. The measured value was 80% of the impedance and the current range was 1 A.

[0083] 0.02 mol / L of phenol was added to the cathode, and after it was fully dissolved, the catalyst activity was measured again by linear sweep voltammetry. Then, its stability was measured by chronopotentiometry (CP). The reaction took 5 hours, and samples were taken every 30 minutes for analysis.

[0084] Example 1

[0085] A carbon-supported nano alloy catalyst: PdFeCuCoNi / C, the preparation method of which comprises the following steps:

[0086] S1. Preparation of catalyst precursor:

[0087] S1-1, 40.5 mg Na2PdCl4 was dissolved in 6 mL of hydrochloric acid solution with a pH of 6 to obtain Pd 2+ Solution; 53mgNiSO4.6H2O, 55mgFeSO4.7H2O, 56mgCoSO4.7H2O, 50mgCuSO4.5H2O were dissolved in 20mL of pH 6 hydrochloric acid solution to obtain Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+Solution;

[0088] Pd 2+ Solution, Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ 2 mL of each solution was mixed in a three-necked flask and ultrasonically dispersed for 10 min to obtain a mixed solution;

[0089] S1-2, add 114 mg of carbon powder to the mixed solution, ultrasonicate for 15 min, fill the three-necked flask with argon, heat and stir at 50 °C for 30 min under argon protection, inject 3 mL of 0.1 mol / L sodium borohydride solution under closed conditions, heat and stir at 50 °C for 13 h under argon atmosphere;

[0090] S1-3. After the reaction is completed, the intermediate product is collected by centrifugation at 10000 rpm for 20 min, and the intermediate product is washed three times with deionized water at 10000 rpm for 5 min each time, and then the intermediate product is dried under argon protection for 8 h to obtain a catalyst precursor; wherein the drying temperature is 110°C and the heating rate is 4°C / min;

[0091] S2. The catalyst precursor was heated to 400-900°C at a heating rate of 4°C / min in a mixed atmosphere of H2 and Ar, reduced for 2 hours, and cooled to room temperature to obtain a carbon-supported nano-alloy catalyst, denoted as PdFeCuCoNi / C.

[0092] In this embodiment, reduction was carried out at 900°C, 650°C and 400°C, respectively, to prepare three catalyst samples, which were respectively recorded as PdFeCuCoNi / C-900°C, PdFeCuCoNi / C-650°C and PdFeCuCoNi / C-400°C for subsequent experiments.

[0093] Performance characterization and testing:

[0094] 1. Characterization results of PdFeCuCoNi / C nanocatalyst

[0095] The crystal structure of PdFeCuCoNi / C was studied by XRD characterization. Figure 1 ). The broad peak at 25° corresponds to the carbon support. No other metal diffraction peaks appeared at 400°C, and an alloy solid solution was formed at this time. Other smaller diffraction peaks appeared at 650°C, and the multi-component alloy solid solution began to transform into an intermetallic compound. Compared with the alloy catalyst at 650°C, the half-peak width of the diffraction peak of the PdFeCuCoNi / C catalyst at 900°C became higher, indicating that the alloy particles became larger at 900°C and an intermetallic compound structure was formed.

[0096] 2. Catalyst reaction performance evaluation results

[0097] The electrocatalytic hydrogenation performance of the prepared PdFeCuCoNi / C catalyst was evaluated by MCV and LSV methods under acidic conditions. For comparison, hydrogen evolution reaction was also carried out in the absence of phenol.

[0098] First, the catalyst was activated at a reduction temperature of 400°C using cyclic voltammetry. After five cycles, the current-potential curve was stable and the five cycle curves tended to overlap ( Figure 2 a), indicating that the stability and activity of the working electrode after activation are improved. This example also determines whether the polarization curve of the PdFeCuCoNi / C catalyst is IR compensated ( Figure 2 b) This curve shows that the performance of the catalyst is not much different with or without IR compensation. At 400°C, the PdFeCuCoNi / C catalyst has a 10 mA cm -2 After adding 20 mM phenol, the potential of PdFeCuCoNi / C shifted significantly to the left by only -0.29 V, with an absolute value of 0.02 V ( Figure 2 c). This indicates that the electrocatalytic phenol hydrogenation reaction is better than the electrocatalytic hydrogen evolution reaction, and the PdFeCuCoNi / C catalyst has better reaction performance.

[0099] Similarly, the PdFeCuCoNi / C catalyst at 650 °C was first activated by MCV ( Figure 3 a), the stability and activity of the working electrode are improved after activation. Then the LSV evaluation is carried out to see whether the catalyst is subjected to IR compensation test ( Figure 3 b) There is little difference between the performance of IR compensation and that of non-compensation. The catalyst at 650℃ reduction temperature has a 10mA cm at -0.28V. -2 After adding 20 mM phenol, the potential of PdFeCuCoNi / C significantly shifted to the left to -0.20 V, and its absolute value was 0.08 V ( Figure 3 c). This indicates that phenol ECH is superior to HER (hydrogen evolution reaction) and has better reaction performance for PdFeCuCoNi / C catalyst.

[0100] The PdFeCuCoNi / C catalyst was first activated by MCV at 900 °C ( Figure 4 a), the stability and activity of the working electrode are improved after activation. Then the LSV evaluation is carried out to see whether the catalyst is subjected to IR compensation test ( Figure 4 b) There is little difference in performance between IR compensation and non-compensation. The catalyst at 900℃ reduction temperature has a 10mA cm above -0.36V. -2 High catalytic current density ( Figure 4 c). After adding 20 mM phenol, the potential of PdFeCuCoNi / C significantly shifted to the left to -0.26 V, and its absolute value was 0.10 V. This shows that phenol ECH is better than HER and has better reaction performance for PdFeCuCoNi / C catalyst.

[0101] Comparison of the polarization curves of PdFeCuCoNi / C catalyst before and after the addition of phenol at different reduction temperatures ( Figure 5 ), which indicates that the catalyst has the largest potential at 900 °C, the highest stability and the best catalytic performance.

[0102] This example focuses on the reaction of selective hydrogenation of phenol to cyclohexanone, and prepares a highly active and highly selective PdFeCuCoNi / C nanocatalyst. The main conclusions obtained through the following performance characterization and testing are as follows:

[0103] 1. PdFeCuCoNi / C high entropy nanocatalyst was synthesized by combining liquid phase reduction and high temperature heat treatment, and its performance was tested in electrocatalytic phenol hydrogenation. The results showed that the catalytic performance of the catalyst was closely related to its reduction temperature. The selectivity of the alloy nanocatalyst for cyclohexanone was poor at a reduction temperature of 400°C, followed by activity and stability at 650°C, and the conversion rate and selectivity were the best at 900°C.

[0104] 2. Through XRD characterization, it was found that after the catalyst was reduced at different temperatures, an alloy solid solution was formed at 400°C, and the multi-component alloy solid solution began to transform into the form of an intermetallic compound at 650°C. Compared with the alloy catalyst at 650°C, the alloy particles became larger at 900°C, forming an intermetallic compound structure.

[0105] In summary, this example describes an effective strategy that enables electrocatalytic hydrogenation with excellent catalytic stability, which can be attributed to the combined effects of highly ordered crystal structure and high entropy and stable PdFeCuCoNi / C nanocatalysts. The ordered structure-performance relationship established in this example will provide guidance for the rational design of catalysts and facilitate further research on multi-component intermetallic materials for electrocatalysis.

[0106] Example 2

[0107] A carbon-supported nano alloy catalyst: PtFeCuCoNi / C, the preparation method of which comprises the following steps:

[0108] S1. Preparation of catalyst precursor:

[0109] S1-1, dissolve 180 mg H2PtCl6·6H2O in 20 mL of hydrochloric acid solution with a pH of 5 to 6 to obtain Pt4+ Solution; 53mg NiSO4.6H2O, 55mg FeSO4.7H2O, 56mg CoSO4.7H2O, 50mg CuSO4.5H2O were dissolved in 20mL of hydrochloric acid solution with a pH of 5-6 to obtain Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ Solution;

[0110] Pt 4+ Solution, Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ 2 mL of each solution was mixed in a three-necked flask and ultrasonically dispersed for 10 min to obtain a mixed solution;

[0111] S1-2, add 114 mg of carbon powder to the mixed solution, ultrasonicate for 15 min, fill the three-necked flask with argon, then heat and stir at 50 °C for 30 min under argon protection, inject 3 mL of 0.1 mol / L sodium borohydride solution under closed conditions, heat and stir at 50 °C for 13 h under argon atmosphere;

[0112] S1-3. After the reaction is completed, the intermediate product is collected by centrifugation at 10000 rpm for 20 min, and the intermediate product is washed three times with deionized water at 10000 rpm for 5 min each time, and then the intermediate product is dried under argon protection for 8 h to obtain a catalyst precursor; wherein the drying temperature is 80°C and the heating rate is 4°C / min;

[0113] S2. The catalyst precursor was heated to 400-900°C at a heating rate of 4°C / min in a mixed atmosphere of H2 and Ar, reduced for 2 hours, and cooled to room temperature to obtain a carbon-supported nano-alloy catalyst, denoted as PtFeCuCoNi / C.

[0114] In this embodiment, reduction was carried out at 900°C, 650°C and 400°C, respectively, to prepare three catalyst samples, which were respectively recorded as PtFeCuCoNi / C-900°C, PtFeCuCoNi / C-650°C and PtFeCuCoNi / C-400°C for subsequent experiments.

[0115] Performance characterization and testing:

[0116] 1. Characterization results of catalyst PtFeCuCoNi / C

[0117] The crystal structure of PtFeCoCuNi nanocrystals supported on carbon was studied by powder X-ray diffraction (XRD). Figure 6 As shown. The XRD pattern of the reduced sample at 900°C exhibits an intermetallic compound, and the peaks at 25.0° and 33.8° are typical characteristics of ordered intermetallic compounds, namely superlattice peaks. When T is reduced to 650°C, the XRD pattern of the sample exhibits a solid solution. When the temperature is 400°C, in the absence of superlattice peaks, the XRD pattern of the sample shows that some metal elements may not be completely reduced. This example notes that at 650°C, the XRD image does not have the characteristic superlattice peaks of the intermetallic structure, but only the characteristic superlattice peaks of the single-phase disordered solid solution alloy. In contrast, an ordered structure is only formed when T is increased to 900°C. Therefore, this example believes that a temperature greater than or equal to 900°C is crucial to ensure sufficient external energy to overcome the obstacles to chemical ordering transformation.

[0118] 2. Catalyst reaction performance evaluation results

[0119] Under acidic conditions, after five cycles of scanning at 400 °C by MCV activation, the shape of the current-potential curve is stable as Figure 7 a shows that the stability of the electrode is improved, and the reaction activity of the electrode is improved after activation. In addition, this example also studies the polarization curve of the PtFeCuCoNi / C electrocatalyst and measures whether iR compensation is performed. Figure 7 b. The results show that the performance of the compensated iR is no different from that of the uncompensated one in terms of HER activity. The activity of the catalyst was also measured by LSV. For comparison, the iR compensation measurement with phenol added was Figure 7 c. The catalytic current density of PtFeCuCoNi / C over the reversible hydrogen electrode (RHE) over -0.30V is 10mA / cm-2. After adding 20mM phenol, its potential shifted significantly to the left to -0.24V, which is at least 150mV less than HER. The catalyst was also tested without LSV compensation with or without the addition of phenol, but no such obvious change was observed, indicating that PtFeCuCoNi / C has the largest potential shift. The above phenomena indicate that phenol ECH is more active than HER on the PtFeCuCoNi / C alloy catalyst.

[0120] This example also carried out the above measurement on the 650°C catalyst. The MCV results are as follows: Figure 8 As shown in a, the surface electrode stability and activity are improved. In the LSV measurement without adding phenol iR compensation, Figure 8 b, In terms of HER performance, the iR performance after compensation is no different from that after uncompensation. In addition, the catalytic current density of PtFeCuCoNi / C over -0.34V is 10mA / cm-2. After adding 20mM phenol, Figure 8 c, its potential shifts to the left to -0.23 V.

[0121] This example also carried out the above measurement on the catalyst at 900°C. The MCV results are as follows: Fig. 9 As shown in a, the surface electrode stability and activity are improved. In the LSV measurement without adding phenol iR compensation, Fig. 9 b, In terms of HER performance, the iR performance after compensation is the same as that after uncompensation. In addition, the catalytic current density of PtFeCuCoNi / C over -0.38V RHE is 10mA / cm -2 After adding 20 mM phenol Fig. 9 c, its potential shifts to the left to -0.21 V.

[0122] The catalysts reduced at three different temperatures were analyzed ( Fig.10 ), it can be seen that the potential shift is the largest when the catalyst is reduced at 900°C, thus it can be concluded that the catalyst reduced at 900°C has the best ECH performance.

[0123] According to the above performance test and characterization results, it can be found that the catalytic activity of the PtFeCoNiCu / C alloy catalyst reduced at 900°C is high. In terms of electrochemical catalysis, the specific surface area of ​​PtFeCoNiCu / C has a uniform porous structure, which maximizes the number of exposed active sites and provides low-resistance diffusion channels. Therefore, the platinum-based alloy catalyst exhibits superior ECH performance, has significant activity and stability, and is therefore able to convert phenol monomer into cyclohexanone and cyclohexanol. This example provides new insights into the design and synthesis of highly active and stable electrocatalysts through alloy doping strategies, and may provide possibilities for the future hydrogenation of phenol into other valuable chemicals and fuels, providing significant advantages for the production of high value-added chemicals.

[0124] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for preparing a carbon-supported nano alloy catalyst, characterized in that: The following steps are involved: S1. Preparation of catalyst precursor: M ion solution, Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ The solutions are mixed and ultrasonically dispersed to obtain a mixed solution; wherein the M ion is Pd 2+ or Pt 4+ ; S1-2, add carbon powder to the mixed solution, perform ultrasonic treatment, then heat and stir under argon protection, inject sodium borohydride solution under closed conditions, and heat and stir to react under argon atmosphere; S1-3, after the reaction is completed, the intermediate product is collected by centrifugation, washed, and then dried under argon protection to obtain a catalyst precursor; S2. The catalyst precursor is heated and reduced in a mixed atmosphere of H2 and Ar, and then cooled to room temperature to obtain a carbon-supported nano-alloy catalyst.

2. The method for preparing a carbon-supported nano alloy catalyst according to claim 1, characterized in that: Step S1-1 is specifically as follows: The salt of M ion is dissolved in hydrochloric acid solution to obtain M ion solution; NiSO4.6H2O, FeSO4.7H2O, CoSO4.7H2O, CuSO4.5H2O are dissolved in hydrochloric acid solution to obtain Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ Solution; M ion solution, Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ The solutions are mixed and ultrasonically dispersed to obtain a mixed solution; Among them, the salt of M ion is Na2PdCl4 or H2PtCl6·6H2O.

3. The method for preparing a carbon-supported nano alloy catalyst according to claim 2, characterized in that: Step S1-1 is specifically as follows: Dissolve 20-360 mg of M ion salt in 3-40 mL of hydrochloric acid solution with a pH of 5-6 to obtain Pd 2+ Solution; 26.5-106mg NiSO4.6H2O, 27.5-110mg FeSO4.7H2O, 28-112mg CoSO4.7H2O, 25-100mg CuSO4.5H2O were dissolved in 10-40mL of hydrochloric acid solution with a pH of 5-6 to obtain Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ Solution; Pd 2+ Solution, Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ Take 1-4 mL of each solution, mix, and ultrasonically disperse for 5-20 minutes to obtain a mixed solution.

4. The method for preparing a carbon-supported nano alloy catalyst according to claim 3, characterized in that: Step S1-2 is specifically as follows: Add 57-228 g of carbon powder to the mixed solution, ultrasonically treat for 5-30 min, then heat and stir at 40-60°C under argon protection for 15-60 min, inject 1.5-6 mL of 0.05-0.2 mol / L sodium borohydride solution under closed conditions, heat and stir at 40-60°C under argon atmosphere for 5-26 h.

5. The method for preparing a carbon-supported nano alloy catalyst according to claim 4, characterized in that: Step S1-3 is specifically as follows: After the reaction is completed, the intermediate product is collected by centrifugation at 5000-20000 rpm for 10-40 min, and the intermediate product is washed with deionized water at 5000-20000 rpm for 2-6 times, each time for 2-10 min, and then the intermediate product is dried under argon protection for 4-16 hours to obtain a catalyst precursor; wherein the drying temperature is 80-110°C and the heating rate is 2-8°C / min.

6. The method for preparing a carbon-supported nano alloy catalyst according to claim 5, characterized in that: Step S2 is specifically as follows: The catalyst precursor is heated to 400-900°C at a heating rate of 2-8°C / min in a mixed atmosphere of H2 and Ar, reduced for 1-4h, and cooled to room temperature to obtain a carbon-supported nano-alloy catalyst.

7. The method for preparing a carbon-supported nano alloy catalyst according to claim 6, characterized in that: in, The salt of the M ion is Na2PdCl4, and the preparation method of the nano alloy catalyst comprises the following steps: S1. Preparation of catalyst precursor: S1-1, 40.5 mg Na2PdCl4 was dissolved in 6 mL of hydrochloric acid solution with a pH of 5 to 6 to obtain Pd 2+ Solution; 53mgNiSO4.6H2O, 55mgFeSO4.7H2O, 56mgCoSO4.7H2O, 50mgCuSO4.5H2O were dissolved in 20mL of hydrochloric acid solution with a pH of 5-6 to obtain Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ Solution; Pd 2+ Solution, Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ 2 mL of each solution was mixed and ultrasonically dispersed for 10 min to obtain a mixed solution; S1-2, add 114 mg of carbon powder to the mixed solution, ultrasonically treat for 15 min, then heat and stir at 50 °C for 30 min under argon protection, inject 3 mL of 0.1 mol / L sodium borohydride solution under closed conditions, heat and stir at 50 °C for 13 h under argon atmosphere; S1-3. After the reaction is completed, the intermediate product is collected by centrifugation at 10000 rpm for 20 min, and the intermediate product is washed three times with deionized water at 10000 rpm for 5 min each time, and then the intermediate product is dried under argon protection for 8 h to obtain a catalyst precursor; wherein the drying temperature is 110°C and the heating rate is 4°C / min; S2. The catalyst precursor was heated to 400-900°C at a heating rate of 4°C / min in a mixed atmosphere of H2 and Ar, reduced for 2 hours, and cooled to room temperature to obtain a carbon-supported nano-alloy catalyst, denoted as PdFeCuCoNi / C.

8. The method for preparing a carbon-supported nano alloy catalyst according to claim 6, characterized in that: in, The salt of M ion is H2PtCl6·6H2O. The preparation method of the nano alloy catalyst comprises the following steps: S1. Preparation of catalyst precursor: S1-1, dissolve 180 mg H2PtCl6·6H2O in 20 mL of hydrochloric acid solution with a pH of 5 to 6 to obtain Pt 4+ Solution; 53mg NiSO4.6H2O, 55mg FeSO4.7H2O, 56mg CoSO4.7H2O, 50mg CuSO4.5H2O were dissolved in 20mL of hydrochloric acid solution with a pH of 5-6 to obtain Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ Solution; Pt 4+ Solution, Ni 2+ Solution, Fe 2+ Solution, Co 2+ Solution, Cu 2+ 2 mL of each solution was mixed and ultrasonically dispersed for 10 min to obtain a mixed solution; S1-2, add 114 mg of carbon powder to the mixed solution, ultrasonically treat for 15 min, then heat and stir at 50 °C for 30 min under argon protection, inject 3 mL of 0.1 mol / L sodium borohydride solution under closed conditions, heat and stir at 50 °C for 13 h under argon atmosphere; S1-3. After the reaction is completed, the intermediate product is collected by centrifugation at 10000 rpm for 20 min, and the intermediate product is washed three times with deionized water at 10000 rpm for 5 min each time, and then the intermediate product is dried under argon protection for 8 h to obtain a catalyst precursor; wherein the drying temperature is 80°C and the heating rate is 4°C / min; S2. The catalyst precursor was heated to 400-900°C at a heating rate of 4°C / min in a mixed atmosphere of H2 and Ar, reduced for 2 hours, and cooled to room temperature to obtain a carbon-supported nano-alloy catalyst, denoted as PtFeCuCoNi / C.

9. A carbon-supported nano alloy catalyst, characterized in that: It is prepared by the method according to any one of claims 1 to 8.

10. Use of the carbon-supported nano alloy catalyst according to claim 9 in catalyzing the selective hydrogenation of phenol.